1992
DOI: 10.1037/0735-7044.106.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior increases dopamine transmission in the nucleus accumbens and striatum of male rats: Comparison with novelty and locomotion.

Abstract: Extracellular concentrations of dopamine (DA) and its metabolites dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA) were examined concurrently, using in vivo microdialysis, in the nucleus accumbens and dorsal striatum of sexually active male rats during tests of locomotor activity, exposure to a novel chamber, exposure to sex odors, the presentation of a sexually receptive female, and copulation. DA increased significantly in the nucleus accumbens when the males were presented with a sexually rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
193
4
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(212 citation statements)
references
References 44 publications
14
193
4
1
Order By: Relevance
“…These single-unit findings are consistent with the large body of data from microdialysis and voltammetry studies that show that levels of DA release within the prefrontal cortex and nucleus accumbens are elevated under both appetitive [13,32,51] and aversive conditions [13,75,110,113]. A primary aim below is to provide a framework that accounts both for the promiscuous DA response to salient events [57,99] and for the large body of evidence showing that DA disruptions attenuate the impact of rewards (and punishers) on several aspects of behavior and learning [1,29,35,38,58,60,76,100,129].…”
Section: Da Neurons Respond To Salient Unexpected Eventssupporting
confidence: 87%
“…These single-unit findings are consistent with the large body of data from microdialysis and voltammetry studies that show that levels of DA release within the prefrontal cortex and nucleus accumbens are elevated under both appetitive [13,32,51] and aversive conditions [13,75,110,113]. A primary aim below is to provide a framework that accounts both for the promiscuous DA response to salient events [57,99] and for the large body of evidence showing that DA disruptions attenuate the impact of rewards (and punishers) on several aspects of behavior and learning [1,29,35,38,58,60,76,100,129].…”
Section: Da Neurons Respond To Salient Unexpected Eventssupporting
confidence: 87%
“…Microdialysis studies have indicated that dopamine is released into the NAc upon presentation of the female, and remains elevated throughout the display of sexual behavior (Pfaus et al, 1990;Pfaus and Phillips, 1991;Damsma et al, 1992;Wenkstern et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about conditioned responses to environmental cues associated with normal motivated behaviors such as sexual behavior. Sexually experienced male rats display increases in NAc DA when exposed to an estrous female behind a wire mesh (Damsma et al, 1992). However, exposure to bedding soiled by an estrous female also stimulates DA release in the NAc (Mitchell and Gratton, 1991), and it is unknown whether conditioned activation of the mesolimbic system is dependent on olfactory input.…”
Section: Introductionmentioning
confidence: 99%
“…Chemosensory and somatosensory stimuli are two major afferent inputs to MPOA that are relevant for copulation in male rodents (Hull et al, 2002), and it is likely that both contribute to DA release during sexual activity. In male rats, extracellular DA increases in MPOA when a female is presented behind a screen, but mating further stimulates DA release (Damsma et al, 1992;Hull et al, 1995). Schulz et al (2003) showed increased dopaminergic activity in MPOA of adult male hamsters exposed to female pheromones.…”
Section: Discussionmentioning
confidence: 93%
“…Neural pathways from the olfactory bulbs to MPOA are well established. Chemosensory cues from the olfactory mucosa and vomeronasal organs are essential for male hamster sexual behavior (Murphy and Schneider, 1970), and previous studies have established that chemosensory stimuli elicit DA release in various brain regions in male rodents (Pfaus et al, 1990;Damsma et al, 1992;Hull et al, 1995;Schulz et al, 2003). However, MPOA also receives other sensory stimuli during mating, including ascending somatosensory input from the penis (Greco et al, 1998;Truitt and Coolen, 2002;Coolen et al, 2003;Truitt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%